Pemanfaatan Ekstrak Daun Pepaya (Carica papaya L.) terhadap Hama Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) - Christian F.A. Rumende; Christina L. Salaki; James B. Kaligis (COCOS, 2021)
ABSTRACTOne of the pests that are detrimental to maize farmers today is the armyworm (S.frugiperda) which attacks maize crops. In general, farmers use chemical insecticides whichare effective but very dangerous to the health of the body and the environment. Carica papayais a plant whose leaves can be used as a botanical insecticide because the secondarymetabolite compounds in these plants can be used as insecticides. The purpose of this studywas to determine the effect of papaya leaf extract on the mortality of S. frugiperda larvae.The method used is data analysis in the form of LC50. In this test using a solutionconcentration of 100 grams/L, 300 grams/L, 500 grams/L, and 700 grams/L with fourrepetitions. The results of the observation of mortality from 24 hours to 96 hours aftertreatment with a solution concentration of 700 grams/L were the solutions that had thegreatest mortality, namely 100% and from the LC50 calculation, the value was 35.457%.This is due to the content of papaya leaf extract which is gastric poison, respiratory poisonand contact poison that can kill S. frugiperda larvae. Papaya leaves can be an alternative toinsecticide for controlling the pest of S. frugiperda.Keywords: Botanical Insecticide, LC50, Mortality.